Physiological Effects of a Tallow-Incorporated Diet Supplemented With an Emulsifier and Microbial Lipases on Broiler Chickens - Wickramasuriya, Samiru Sudharaka; Macelline, Shemil Priyan; Cho, Hyun Min; Hong, Jun Seon; Park, Seung Hwan; Heo, Jung Min (Frontiers in Veterinary Science, 2020)
The aim of this study was to investigate the effect of dietary emulsifiers and lipase supplementation on growth performance, blood metabolites, intestinal organ weight, gut morphology, nutrient digestibility, carcass measurements, and meat quality in broiler chickens. A total of 384, 1-day-old Ross 308 broiler chicks were randomly allocated to one of eight dietary treatments arranged in a completely randomized design with 6 replications per treatment and 8 birds per cage. Diets were corn-soybean meal-based and formulated to meet the nutritional requirements for Ross 308 specifications. Beef tallow used as the fat source in all diets. Dietary treatments were as follows: (1) positive control (PC; energy sufficient diet); (2) negative control (NC; energy deficient, -100 ME, kcal/kg); (3) NC+POL (0.1%, Polysorbate-20); (4) NC+CET (0.1%, Ceteth-20); (5) NC+POL+TLL (0.1%, Thermomyces lanuginosus lipase); (6) NC+POL+CRL (0.1%, Candida rugosa lipases); (7) NC+CET+CRL and (8) NC+LL (0.05%, Lysolecithin). Growth performances were measured weekly. One bird per pen was selected and sacrificed to collect blood, ileal digesta, jejunum sample, viscera organ weight, and meat samples on day 21 and 35. Results revealed that birds fed NC+POL+CRL diet had higher (P<0.05) body weight, weight gain, and the improved (P<0.05) feed efficiency compared to birds fed other low energy diets, and the effect was more prominent at the grower phase from day 21 to 35. Similarly, higher (P<0.05) villi height and lower (P<0.05) crypt depth commensurate with higher (P<0.05) V:C ratio were observed with the broiler chickens fed NC+POL+CRL diet compared to broiler chickens fed NC diet on day 21 and 35. Moreover, broiler chickens fed NC+POL+CRL diet showed improved fat and energy digestibility compared NC diet counterpart on day 35. This study, therefore indicated that Polysorbate-20 together with Candida rugosa lipases had promising ability to improve growth performance of broiler chickens fed with low energy diet and curtail the growth depression without affecting blood metabolites, carcass, and visceral organs weights.